Analisis Kinerja Keuangan Perusahaan dengan Menggunakan Economic Value Added (EVA) dan Market Value Added (MVA) Studi pada Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2007-2011 - Rosihana, Athiy Dina; lendro, Har (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Competition in the business world so that more and more stringent assessment of the company's performance be measured by the success of a company. Assessment of the company's performance is measured by using the method of (Economic Value Added) and EVA (Market Value Added) MVA using data from income statements and balance sheets,Â stock market returns, stock prices, stock index, the number of shares outstanding, and SBI. Telecommunications sector to attract the object of research for the development of this sector is very rapid. In addition, people are now very dependent to telecommunications companies because of the convenience offered by them. EVA two companies generated positive (+) indicates that the company has managed to create wealth for shareholders and the company. MVA both companies is positive (+) means that the managementÂ has been able to increase the wealth of the company and its shareholders and the financial performance of the company is in good condition. Keyword : Financial Performance, Economic Value Added, Market Value Added